2017
DOI: 10.1158/1535-7163.mct-17-0030
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Targets hnRNPA1 to Overcome Enzalutamide Resistance in Prostate Cancer Cells

Abstract: Prostate cancer remains dependent on androgen receptor signaling even after castration. Aberrant androgen receptor signaling in castration resistant prostate cancer is mediated by mechanisms such as alterations in the androgen receptor and activation of interacting signaling pathways. Clinical evidence confirms that resistance to the next generation anti-androgen, enzalutamide, may be mediated to a large extent by alternative splicing of the androgen receptor to generate constitutively active splice variants s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…12,13 Meanwhile, it was reported that Que downregulated heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) expression and sensitized enzalutamide to kill prostate cancer cells; thus, Que and enzalutamide worked synergistically in this treatment. 14 In this study, we combined Que and PTX to treat prostate cancer, and we evaluated the in vitro and in vivo antitumor effects. In the in vitro study, we analyzed cancer cell proliferation, apoptosis, cell cycle arrest, and ROS production after the cancer cells were treated with both Que and PTX.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Meanwhile, it was reported that Que downregulated heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1) expression and sensitized enzalutamide to kill prostate cancer cells; thus, Que and enzalutamide worked synergistically in this treatment. 14 In this study, we combined Que and PTX to treat prostate cancer, and we evaluated the in vitro and in vivo antitumor effects. In the in vitro study, we analyzed cancer cell proliferation, apoptosis, cell cycle arrest, and ROS production after the cancer cells were treated with both Que and PTX.…”
Section: Introductionmentioning
confidence: 99%
“…The compounds are often responsible for certain unique plant characteristics, including smell and pigmentation, and a number are vital for the protection of the host against parasites, viruses and other externally damaging agents. Moreover, phytochemicals could be compounds of interest in cancer chemoprevention due to their lower toxic effects compared with conventional chemotherapeutic drugs, their action on molecular targets involved in carcinogenesis (18) or their resensitizing effects on antiandrogen-resistant cells (19). An inverse correlation between consumption of cruciferous vegetables and cancer risk has been observed in PC and breast, colon, lung and gastric cancer (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that hnRNPA1 is highly expressed in prostate tumors, compared to benign prostates, and upregulates the expression of AR-V7 [90]. Furthermore, it was shown that the downregulation of hnRNPA1 by quercetin, a flavonoid abundantly present in plants, concomitantly decreases the expression of AR-V7, resensitizing enzalutamide-resistant prostate cancer cells to enzalutamide treatment in mouse xenografts [91]. However, another study suggested that hnRNPA1 suppresses AR-V7 expression in prostate cancer cells [92].…”
Section: Hnrnpsmentioning
confidence: 99%
“…It was reported that histone demethylase jumonji domain containing 1A (JMJD1A) recruits hnRNPF onto the region around the 5' side of AR exon 3B, and JMJD1A and hnRNPF support the recruitment of splicing factors including U2AF 65 to the 3' SS in front of exon 3B, which leads to the inclusion of exon 3B to produce AR-V7 [89]. Moreover, another hnRNP family member hnRNPA1 is suggested to be involved in AR-V7 expression [90][91][92]. It was previously reported that hnRNPA1 is highly expressed in prostate tumors, compared to benign prostates, and upregulates the expression of AR-V7 [90].…”
Section: Hnrnpsmentioning
confidence: 99%